Understanding protein variability through functional analysis of random mutagenesis - Kaplan, Andrew (Henry Stewart Talks, 2007)
Random mutagenesis, Strategies, Single template: oligonucleotide-based and PCRbased strategies, Recombination-based strategies, Bias, MAX codons, Random mutagenesis of an entire gene, Mutagenesis due to PCR error, Non-homologous recombination strategies